Maize and Pigeonpea Intercropping - Selian Agriculture Research Institute; International Center for Tropical Agriculture (International Food Policy Research Institute, 2017)
The project tested different spatial maize/pigeon peas arrangements in the field with already recommended varieties that are differentiated by maturity periods (which affect canopy interactions). The maize varieties included PAN 691, a long maturing maize variety, Mkombozi, an early to medium maturity high yielding maize variety, and SC 627, an early maturing variety. These were intercropped with pigeon peas variety Mali from ICRISAT, a long maturing and high yielding variety that was considered new in the study sites. Project title: Research in Sustainable Intensification in the Sub-Humid Maize-Based Cropping Systems of Babati. Project abstract: Promoting sustainable intensification through efficient application of a local source of phosphorus (Minjingu PR). Project website: http://africa-rising.net